What went wrong? The evolution of the IMF 1941-1961 - PRESSNELL, L.S. (PSL Quarterly Review, 2013)
Despite its promising start in 1946-47, the new IMF soon ceased to fulfil its expected role for almost nine years. An exploration is provided for the latter in the wider context of international economic cooperation. It was not until 1961 that the Fund's intended status as 'the focal point of monetary decisions' was really achieved. JEL Codes: F02, F33